Disposition and metabolism of N-butylbenzenesulfonamide in Sprague Dawley rats and B6C3F1/N mice and in vitro in hepatocytes from rats, mice, and humans. (1st February 2020) - Waidyanatha, Suramya; Black, Sherry R.; Patel, Purvi R.; Rider, Cynthia V.; Watson, Scott L.; Snyder, Rodney W.; Fennell, Timothy R.
Highlights: N -Butylbenzenesulfonamide (NBBS) is a plasticizer detected in the environment. This work describes the disposition of NBBS in rodents following oral exposure. NBBS was well-absorbed in rodents and excreted mainly via urine. It was well-distributed to tissues. NBBS was metabolized to numerous metabolites including oxidative metabolites. Abstract: N -Butylbenzenesulfonamide (NBBS) is a plasticizer detected in the environment suggesting potential human exposure. These studies investigated the in vitro hepatic clearance and disposition of [ 14 C]NBBS in rodents following a single gavage (2, 20 or 200 mg/kg) or intravenous (IV) administration (20 mg/kg). NBBS was cleared slower in hepatocytes from humans compared to rodents. [ 14 C]NBBS was well-absorbed in male rats following gavage administration and excreted extensively in urine (70–76 %) and feces (11–15 %) 72 h following administration. Following a 20 mg/kg gavage dose in male rats, 25 % of the dose was excreted in bile by 24 h suggesting that observed fecal excretion was due to biliary excretion. The radioactivity was distributed to tissues with 14 % and 8 % of the administered dose remaining in tissues at 24 and 72 h, respectively. There was no apparent dose-dependent effect in disposition in male rats. Disposition patterns were similar in female rats (urine, 83 %; feces, 14 %) and male (urine, 69 %; feces, 11 %) and female (urine, 72 %; feces, 9 %) mice following gavage administration of 20 mg/kg. The disposition following IV administration was similar to that of gavage. Urinary radiochemical profiles were similar between doses, routes, species, and sexes. Among numerous metabolites identified, oxidative metabolites of NBBS predominated.